2015
DOI: 10.1136/injuryprev-2015-041814
|View full text |Cite
|
Sign up to set email alerts
|

All Wales Injury Surveillance System revised: development of a population-based system to evaluate single-level and multilevel interventions

Abstract: BackgroundInjury surveillance has been established since the 1990s, but is still largely based upon single-source data from sentinel sites. The growth of electronic health records and developments in privacy protecting linkage technologies provide an opportunity for more sophisticated surveillance systems.ObjectiveTo describe the evolution of an injury surveillance system to support the evaluation of interventions, both simple and complex in terms of organisation.MethodsThe paper describes the evolution of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…The pattern of incidence of UI attendance found in this study is identical to that found in Wales for all injuries, in particular the same highest and lowest rates for 10–14 and 65–69 years old, respectively, are evident in both settings 29. Other studies have also found similar patterns with respect to inequality, in particular sharp increases in injury rates among the most deprived.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The pattern of incidence of UI attendance found in this study is identical to that found in Wales for all injuries, in particular the same highest and lowest rates for 10–14 and 65–69 years old, respectively, are evident in both settings 29. Other studies have also found similar patterns with respect to inequality, in particular sharp increases in injury rates among the most deprived.…”
Section: Discussionsupporting
confidence: 85%
“…In Wales, the All Wales Injury Surveillance System is used to evaluate injury prevention initiatives on a population scale, the effect of which may be too small to pick up in a small-scale trial or survey 29. In England, the Information Sharing to Tackle Violence initiative allows hospitals to share non-confidential ED data with Community Safety Partnerships in turn allowing police to target and prevent violent injuries in the community 34.…”
Section: Discussionmentioning
confidence: 99%
“…For the surveillance of cancer, data linkage not only provides the opportunity to improve the population-based screening [31] but it also helps to detect different types of cancer recurrence [32] and to evaluate the socioeconomic status of patients with cancer (e.g., return to work) [33]. Linked data also allows evaluating the health interventions at various levels of the population [34]. The diversity and the volume of health information have been increasing rapidly and push to discover new parameters to improve population health with innovative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…interventions to specific injury groups and populations. Regional and national injury surveillance systems in high-and middle-income countries are well established; however systems often use data captured in hospitals only (Nelson et al 2011;Crain et al 2016;Lyons et al 2016). To our knowledge, this is the only published research in scientific journals that uses ambulance records to study child injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Such data sources are used in various regional and national injury surveillance systems, e.g. Trauma and Injury Intelligence Group, England (Quigg et al 2012); All Wales Injury Surveillance System (Lyons et al 2016); National Electronic Injury Surveillance System, USA (Nelson et al 2011); Canadian Hospitals Injury Reporting and Prevention Program (Crain et al 2016). A few studies have shown some utility in the use of ambulance service data in injury surveillance; whilst not solely focused on children, they indicate that such data could also be used to develop understanding and monitoring of injury at local and regional levels (Backe and Andersson 2008;Thomas et al 2011;Quigg et al 2017).…”
Section: Introductionmentioning
confidence: 99%